2004
DOI: 10.1103/physrevd.69.036003
|View full text |Cite
|
Sign up to set email alerts
|

CPviolation in weak interactions from orbifold reduction: Possible unification structures

Abstract: We present a mechanism to generate complex phases from real 4 + 1 dimensional couplings in a model of weak interactions through dimensional reduction of a gauge theory. The orbifolding of a 4 + 1 dimensional Sp(4) × U (1) group is the minimal setup which provides both CP violation and an SU (2) × U (1) structure. We show that grand unification requires at least SO(11).CP violation in the standard model, since gauge interactions are naturally CP symmetric, is provided by complex Yukawa couplings which eventuall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In this case, we have shown that the first usable unification group is SO(11) (rather than the usual SU (5) or SO (10)). The source of this extension is precisely in the need to localize both left-and right-handed fermions.…”
Section: Towards Realistic Models -Chiral Examplesmentioning
confidence: 94%
See 1 more Smart Citation
“…In this case, we have shown that the first usable unification group is SO(11) (rather than the usual SU (5) or SO (10)). The source of this extension is precisely in the need to localize both left-and right-handed fermions.…”
Section: Towards Realistic Models -Chiral Examplesmentioning
confidence: 94%
“…In a simple example, we generate CP violation from a 4+1 theory with only real couplings. This work is based on reference [9], and its generalization to include grand unified structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…(2.13). The total operations on the fermion fields equal to 21) or 22) where we have omitted the subscripts. In the above, beginning with the 6D action eq.…”
Section: Jhep09(2009)091mentioning
confidence: 99%
“…Interestingly, the above CP violation induction via deconstruction can also be visualized in extra dimensional view point. Indeed, because of having the same symmetry transformation property, DD link field can be identified with the Wilson line pointing along a latticized transverse direction (Appendix B), and the latter then can naturally acquire a complex VEV in the generalized Hosotani's mechanism [6,7,8,9] of dynamical symmetry breaking. Apparently, the source of CP violation in this approach comes from the complex effective Yukawa couplings so it can be classified as hard CP violation.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we look specifically into two such important mechanisms of extra dimension theories, namely the localization of matter fields in the bulk [3,4,5] and the dynamical breaking of CP symmetry by ED Wilson line [6,7,8,9]. Ultimately, the hybrid of these two mechanisms is just the well-known complex mixing of fermion flavors.…”
Section: Introductionmentioning
confidence: 99%